(untitled) (European Science Methodical Journal, 2025)
For the work of medical institutions to be effective, not only qualified doctors of various profiles are required, but also competent managers. Healthcare manager is an important and necessary profession in the modern world. Such specialists are in demand both in private clinics and in budget hospitals, dental clinics, and polyclinics.